بين مكسيم غوركي وحنا مينة في ضوء المنهج التاريخي المقارن ( من خلال ثلاثية السيرة الذاتية ) - شرف, نزار (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يستعرض هذا البحث العلاقة بين مكسيم غوركي وحنا مينة (من خلال ثلاثية السيرة الذاتية) بالمنهج التاريخي المقارن للمدرسة الروسية، المنهج الأكثر دقة وشمولاً بما يوليه من اهتمام للعوامل المختلفة التي تسهم في ظهور التشابهات والاختلافات بين الآداب القومية دون التحيز للأدب القومي أو الجور عليه، فهو لا يقصر دراسته على التأثير كما تفعل المدرسة الفرنسية، ولا يتنكر للتأثير كما تفعل المدرسة الأمريكية، بل يرى أن التأثير أشد ما يكون قوة عندما يقع على قاعدة من المتوافقات النمطية فالتأثر العميق والحقيقي لا يحدث إلا عندما يتطلب التطور الأدبي في البلد المتأثر دفعاً وحفزاً، نحو طريق جديدة، وتأثير الآداب الاشتراكية، ولا سيما أدب غوركي، في الأدب العربي كان تلبية للاحتياجات الأدبية في البلدان العربية في مرحلة من مراحل تطور الأدب العربي ونهوضه واكبت تطور الأدب العربي ونهوضه الثوري والاجتماعي. والتأثير الشخصي والفكري والفني لغوركي في حنا كان عميقاً وشاملاً، قواه وحدة مذهبهما الواقعي في الأدب، وتشابه طباع الكابتين ومصيريهما ووحدة مواقعهما العقائدية، ومواجهة كل منهما لمهمة واحدة هي تصوير التناقضات الاجتماعية المعقدة في مرحلة من مراحل التغيير الاجتماعي الكبير . This research discusses the relation ship between Maxiem Gorky and Hanna Mena (through out of the tripartite of the personal biography) with the comparative historical method of the Russian school ,this method is the most exact and the most comprehensive one for being interested in the different factors because it participates in the appearance of the similarities and differences among the national literatures without prejudice or oppression to the national literature. It is not restricted to the influence as the French school dose and it does not deny it as the American school but it finds that the influence becomes more powerful when it is built on a basis of pattern agreements so the deep and the real influence does not occur exapt when the affected country needs a drive and a motive towards a new way and the influence of the socialist literatures and especially the literature of Maxiem Ghorky in the Arabian literature was an acceptance to the literary needs in the Arabian countries in a stage of the development of the Arabian literature and its rise which accompany the development and the revolutionary and social rise of the Arbian literature. The personal intellectual and artistic influence of Ghorky in Hanna was deep and comprehensive and it was supported by the union of their realistic schools in literature the similarities of the authors tempers and their destiny ,the union of their ideological positions and the confrontation of each one of them to a single task which is a portrayal of the complex and social opposites in a stage of great social trans foration once 0